Comparison of Fully Automated and Semiautomated Systems for Protein Immunofixation Electrophoresis. Issue 2 (18th July 2016) - Napodano, Cecilia; Pocino, Krizia; Gulli, Francesca; Colacicco, Luigi; Santini, Stefano Angelo; Zuppi, Cecilia; Basile, Umberto
Abstract : Background: In order to establish a diagnosis of monoclonal gammopathy, it is necessary to detect and identify monoclonal components. To confirm the immunological nature of the proteins, the next step is to define their composition in heavy and light chains using immunofixation. The purpose of this study was to compare two different instruments, one semiautomated and the other fully automated for serum and urine immunofixation. Methods: We selected 150 sera and 100 urines from patients admitted for routine analysis, which were analyzed by immunofixation to characterize monoclonal components. Results and conclusion: Comparison study showed a difference in the identification of small monoclonal components and hypogammaglobulinemia, in serum and urine, between the two analyzers. We also observed a difference in the length of the electrophoretic pattern that is of considerable importance as it leads to a better resolution of the gamma region, allowing to identify even the smallest monoclonal component that can be easily hide in an oligoclonal pattern. For this reason, there is need to ameliorate commercial immunofixation assays. It is essential to improve data harmonization and standardize measurement procedures in order to guarantee a correct diagnosis for the right patient care.